1997
DOI: 10.1021/ja9643634
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear Metal Hydrido Alkoxides. 2. Hydrogenation of 1,2-W2(iBu)2(OiPr)4. Preparation, Characterization, and Some Reactions of W6H5(CiPr)(OiPr)12, W2(H)2(OiPr)4(dmpe)2, and W4(H)4(dmpm)3, Where dmpe = Bis(dimethylphosphino)ethane and dmpm = Bis(dimethylphosphino)methane

Abstract: H2 and 1,2-W2(iBu)2(OiPr)4 react in hydrocarbon solvents to give the cluster W6(H)5(CiPr)(OiPr)12 (1) in 40% crystalline yield. W2(H)2(OiPr)4(dmpe)2 (2) and W4(H)4(OiPr)8(dmpm)3 (3) have been isolated in the presence of the chelating diphosphines Me2PCH2CH2PMe2 (dmpe) and Me2PCH2PMe2 (dmpm). Reactions involving the use of various isotopes reveal the importance of both α- and β-CH activation of the iBu ligand. An X-ray determination and NMR data reveal that 1 contains an octahedral W6 unit, W−W = 2.58 to 2.85 Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In marked contrast, elimination of CH 3 ZnO-i-C 3 H 7 is almost negligible for the trinuclear zinc cluster [(CH 3 ) 2 Zn 3 (O-i-C 3 H 7 ) 3 ] 1 (m/z ¼ 399 for the 64 Zn 3 isotope) whose fragmentation occurs in two different ways. The predominating route leads to loss of neutral acetone, (CH 3 ) 2 CO, concomitant with an ionic fragment to which we tentatively assign the structure of a hydrido-metal alkoxide, 32 i.e., 2). A minor, but yet notable route involves the elimination of a neutral entity with Dm ¼ À80 for 64 Zn; corresponding mass shifts are observed for ions containing other zinc isotopes.…”
Section: Experimental Methodsmentioning
confidence: 81%
“…In marked contrast, elimination of CH 3 ZnO-i-C 3 H 7 is almost negligible for the trinuclear zinc cluster [(CH 3 ) 2 Zn 3 (O-i-C 3 H 7 ) 3 ] 1 (m/z ¼ 399 for the 64 Zn 3 isotope) whose fragmentation occurs in two different ways. The predominating route leads to loss of neutral acetone, (CH 3 ) 2 CO, concomitant with an ionic fragment to which we tentatively assign the structure of a hydrido-metal alkoxide, 32 i.e., 2). A minor, but yet notable route involves the elimination of a neutral entity with Dm ¼ À80 for 64 Zn; corresponding mass shifts are observed for ions containing other zinc isotopes.…”
Section: Experimental Methodsmentioning
confidence: 81%
“…Two other clusters derived from (M⋮M) 6+ centers warrant mention. The hydrogenation of W 2 ( i Bu) 2 (O i Pr) 4 in hydrocarbon solvents leads to a most unusual cluster hydride: W 6 (H) 5 (C i Pr)(O i Pr) 12 . This compound was originally formulated as W 6 (H) 5 (O i Pr) 13 , but a more carefully crystallographic refinement and a detailed 13 C [ 1 H] study revealed the presence of the μ-C i Pr ligand.…”
Section: M2 Starting Materials With a Bond Order Ofmentioning
confidence: 99%
“…Therefore, the design of auxiliary ligand systems provides an attractive avenue to explore hydride complexes with novel properties. For early transition metals, hydride species have played a crucial role in studying olefin hydrogenation, polymerization, and CO reduction. , While most of them contain the cyclopentadienyl ligand and its substituted derivatives, there is a highly reactive class of compounds incorporating O-donor ligands such as alkoxide, aryloxide, or siloxide ligands due to their coordinative unsaturation. Rothwell and co-workers reported that niobium and tantalum hydride species supported by bulky aryloxide ligands were implicated in catalytic hydrogenation of polycyclic aromatic hydrocarbons with good chemoselectivity and stereoselectivity .…”
Section: Introductionmentioning
confidence: 99%